From ceremonial to social interventionism: An examination of media coverage of Ghana’s Second Lady, Samira Bawumia: From ceremonial to social interventionism: An examination of media coverage of Ghana’s Second Lady, Samira Bawumia - Sikanku, G. Etse; Donkor, Louise (Drumspeak: International Journal of Research in the Humanities, 2024)
This research analyzed media framing of Ghana’s second lady, Samira Bawumia. Although the office and stature of the second lady has evolved over time, there is a clear paucity of literature investigating how such a high-profile personality has been covered in the media. A media framing analysis of news reports revealed six frames in the coverage of the second lady. These include spousal frame, which was the most predominant, followed by the social intervention frame, the political frame, policy frame, ceremonial frame and fashion frame. The tone of coverage was largely positive while thematic frames dominated as compared to episodic frames. A significant finding from the study was that the media ignored divergent sources with experts and civil society minimally sourced stories while non-sourced stories were prevalent. This study demonstrates that while media coverage is improving in terms of the tone and direction of coverage for high profile female personalities, more needs to be done in terms of training and capacity building to improve the nature of gender-based reportage.